الاحتياجات التدريبية لمعلمات تعليم الكبيرات بشرق مدينة الرياض - الشهري، زانة بنت عبدالله; درويش، حنان محمد محمد (مؤسسة د. حنان درويش للخدمات اللوجستية والتعليم التطبيقي, 2020)
هدفت الدراسة الحالية إلى 1-التعرف على مدى مساهمة التدريب في تطوير الأداء المهني لمعلمات تعليم الكبيرات. 2-التعرف على أهمية اهتمام إدارة التعليم في عملية التدريب المهني لمعلمات تعليم الكبيرات. 3-التعرف على دور إدارة التعليم في تطوير الأداء المهني لمعلمات تعليم الكبيرات. 4-التعرف على العناصر الأساسية (الاحتياجات التدريبية) لتحقيق فاعلية التدريب المهني لمعلمات تعليم الكبيرات. 5-التعرف على المشكلات التي تواجه العملية التدريبية لمعلمات تعليم الكبيرات واقترحت سيناريوهات المستقبل الاستشرافية التي بدأت بسيناريو النظرة التشاؤمية مرورا بسيناريو النظرة المطمئنة ثم النظرة الإيجابية وصولا إلى النظرة الاستشرافية المستقبلية الممكنة والمرغوبة. The current study aimed to 1-To identify the extent of the training's contribution to the development of the professional performance of adult female teachers. 2-Recognizing the importance of the education administration's interest in the process of vocational training for adult female teachers 3-Recognizing the role of the education administration in developing the professional performance of adult female teachers. 4-Identifying the basic elements (training needs) to achieve the effectiveness of vocational training for adult female teachers. 5-Identifying the problems facing the training process for adult female teachers It suggested forward-looking future scenarios, which began with the pessimistic view scenario, passing through the reassuring view scenario, then the positive view, leading to the possible and desirable future outlook.
Keywords: العملية التدريبية -- الأداء المهني -- إعداد المعلمين -- مدينة الرياض